Analysing the influence of a large flood on eastern redcedar (Juniperus virginiana) distribution along the Missouri River using remote‐sensing techniques. Issue 4 (28th January 2021) - Illeperuma, Nadeesha D.; Dixon, Mark D.
Abstract: River floodplains are among the world's most altered ecosystems due to flow regulation by dams, development, and agriculture. Dam construction and flow regulation along the Missouri River have reduced flooding, modified geomorphic processes and altered floodplain vegetation. Since the commencement of flow regulation, eastern redcedar ( Juniperus virginiana L.), which is native to upland areas, has invaded the understorey of cottonwood ( Populus deltoides ) forests along the Missouri River. A major flood in 2011, however, resulted in a significant die‐off of redcedar within the Missouri National Recreational River (MNRR), South Dakota, and Nebraska, USA. The objectives of this study were to map and analyse the effects of the 2011 flood and soil drainage classes on redcedar distribution within the MNRR. The Normalized Difference Vegetation Index (NDVI) from winter scenes of Landsat satellite imagery was used to map the canopy cover of redcedar on pre‐ and post‐flood dates. Logistic regression was used to analyse the effects of soil drainage and flooding status (flooded or non‐flooded) on transitions between high (>20%) and low (<20%) canopy cover classes of redcedar. The odds of redcedar decline (from high to low canopy cover) were significantly greater in areas that flooded in 2011, and the odds of redcedar increase (low to high canopy cover) were greater on non‐flooded surfaces with well‐drained soils. This study produces evidence that large floods are important for constraining redcedar spread in floodplain habitats. In addition, soil drainage affects redcedar survival and spread within the study area, with colonization favoured on well‐drained soils.